Ahistorizem historične sociologije - Rutar, Tibor (Teorija in praksa, 2015)
Historical sociology of a Weberian, Marxist, Durkheimian or some other bent has, from the start, implicitly followed the view of Adam Smith according to which the perennial expansion of market opportunities, the consolidation of urban centres and the rise of a bourgeois class, the deepening division of labour or the accumulation of wealth was bound up in some fundamental, quasi-automatic way with the development of human history in general, and the historic transition from the pre-modern, pre-capitalist period to the modern, capitalist period in particular. In the article, we show that in the light of some recent developments in contemporary historiography this view is both theoretically and empirically very problematic. What is more, we examine how the mentioned Smithian presuppositions lead to market or technological determinism, teleology and trans-historicity.
Keywords: ahistorizem; Capitalism; Historical sociology; historična sociologija; Kapitalizem; Marksizem; Marxism; Zgodovinska sociologija